Perjalanan Psikologi Tokoh Utama dalam Cerpen Keluarga M Karya Budi Darma: Analisis Psikologi Freudian - Nurfadillah, Atik Azzahra (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
This research aims to determine the psychological journey of the main character in the short story collection People of Bloomington in the short story Keluarga M by Budi Darma, by applying Freud's literary psychology approach. The character investigated is